Hyperendemic human fascioliasis in Andean valleys: An altitudinal transect analysis in children of Cajamarca province, Peru - González, L. Carolina; Esteban, José Guillermo; Bargues, M. Dolores; Valero, M. Adela; Ortiz, Pedro; Náquira, Cesar; Mas-Coma, Santiago (Acta tropica, 2011)
A coprological survey on fascioliasis in school children from rural localities in Peruvian Cajamarca showed very high prevalences, high intensities, high coinfections with other parasites and a significant correlation with altitude. [Display omitted] ► Fascioliasis survey of school children from rural localities in Cajamarca, Peru. ► Very high prevalences and intensities were the highest so far recorded in the area. ► Fascioliasis coinfection with protozoans and other helminths was the rule. ► Fascioliasis prevalence showed a significant correlation with altitude. ► Results suggest that human fascioliasis may be widespread throughout that area. A coprological survey including 476 2–18 year old school children from six rural localities between 2627 and 3061m altitude was performed in Cajamarca province, Peru. Prevalences of fascioliasis ranging from 6.7 to 47.7% (mean 24.4%) proved to be the highest so far recorded in that human hyperendemic area. Higher prevalences in females and in the 2–5 year old group were not significant. Intensities ranged from 24 to 864 eggs per gram (arithmetic mean: 113; geometric mean: 68), the majority shedding less than 100, and without significant differences according to gender or age group. Fasciola hepatica was the most common helminth within a spectrum of 11–12 protozoan and 9–11 helminth species, 97.3% of the children showing infection with at least one parasite. The highest levels corresponded to coinfection with seven different species in females and subjects older than 5 years. Fascioliasis prevalence correlation with altitude appeared significant. An epidemiological characterisation of the valley transmission pattern of fascioliasis in Cajamarca is made by comparison with other better known hyperendemic areas. Results suggest that human fascioliasis may be widespread throughout different parts of Cajamarca province, even far away from the city, and that long-term fascioliasis chronicity and superimposed repetitive infections may be probably frequent.